Women's Empowerment: Pemulihan Perekonomian Indonesia melalui Kelompok Wanita Tani dengan Pengimplementasian Program M2ID - Toni Nurhadianto; Ulfah Tika Saputri; Zulkarnaini Zulkarnaini (Institut Ilmu Sosial dan Manajemen Stiami, 2022)
Corona virus diseases (COVID-19) have a negative impact on the country's economy, and Indonesia is no exception. This is evidenced by the increase in the poverty rate of 1.63 million people. Poverty alleviation can be done by involving the community such as involving people's business actors through the Women Farmers Group (KWT). However, the problem is the weak organizational function and the lack of education of KWT Sehati members on financial management and the difficulty of product marketing. These problems are answered in the M2ID (Management of Human Resources, Management of Finance, Innovation and Packaging, and Digital Marketing) program. The approach methods used in this activity include institutional approaches, discussion methods, participatory approaches, and providing training on the M2ID program. After the training, the average understanding possessed by members increased in understanding, besides that members began to be able to make sales not only offline but online sales and in the end were able to slowly build the Indonesian economy after COVID-19. Keyword: Women’s Empowernment; Indonesian Economics Recovery; Kelompok Wanita Tani